Antioxidant defence and oxidative stress markers in cats with asymptomatic and symptomatic hypertrophic cardiomyopathy: a pilot study - Marcin Michałek (BMC Veterinary Research, 2020)
Abstract Background Hypertrophic cardiomyopathy is the most common cardiovascular cause of death in cats. Although the majority of cats remain asymptomatic, some may develop signs of chronic heart failure due to diastolic failure, arterial thromboembolism (ATE) or sudden cardiac death. Therefore, it is crucial to identify individuals that are in high risk of developing cardiac complications before the onset of life-threatening signs. Oxidative stress is the imbalance between the production and neutralisation of reactive oxygen species. Uncontrolled reactive oxygen species overproduction leads to protein and lipid peroxidation and damages the DNA strands, injuring the cells and leading to their death. The aim of the study was to evaluate the oxidative state in cats with hypertrophic cardiomyopathy and healthy controls. Results In total, 30 cats divided into three groups were assessed: animals with clinically evident hypertrophic cardiomyopathy (HCM; n = 8), subclinical hypertrophic cardiomyopathy (SUB-HCM; n = 11) and healthy controls (n = 11). The activity of superoxide dismutase was statistically significantly lower in animals with symptomatic and asymptomatic hypertrophic cardiomyopathy (HCM 0.99 ± 0.35 U/mL; SUB-HCM 1.39 ± 0.4 U/mL) compared to healthy cats (2.07 ± 0.76 U/mL, p < 0.01). The activity of catalase was significantly lower in the SUB-HCM group (19.4 ± 4.2 nmol/min/mL) compared to the HCM (23.6 ± 5.9 nmol/min/mL) and the control (30 ± 7.5 nmol/min/mL, p < 0.01) group. The activity of glutathione peroxidase was 4196 ± 353 nmol/min/mL in the HCM group, 4331 ± 451 nmol/min/mL in the SUB-HCM group and 4037 ± 341 nmol/min/mL in the control group and did not differ significantly between groups. The total antioxidant capacity of plasma was 602 ± 65.5 copper reducing equivalents (CRE) in the HCM group, 605.9 ± 39.9 CRE in the SUB-HCM group and 629 ± 77.5 CRE in the healthy cats and did not differ significantly between the groups. Conclusions Activities of superoxide dismutase and catalase differed in cats with hypertrophic cardiomyopathy, however the activity of the latter was only significantly lower in asymptomatic stage of the disease. The potentially beneficial effect of antioxidative substances on the disease progression in the asymptomatic and symptomatic stage of this disease should also be examined.